Optical orientation of nematic liquid crystal droplets via photoisomerization of an azodendrimer dopant - Shvetsov, Sergey A.; Emelyanenko, Alexander V.; Boiko, Natalia I.; Zolot'ko, Alexander S.; Zhang, Yan-Song; Liu, Jui-Hsiang; Khokhlov, Alexei R. (Beilstein Journal of Nanotechnology, 2018)
Two sequential transformations of the orientational structure in nematic liquid crystal droplets containing a dendrimer additive (nanosized macromolecules with light-absorbing azobenzene terminal moieties) under light irradiation in the UV–blue spectral range were investigated. The origin of these transitions is in the change of the boundary conditions due to photoisomerization of the dendrimer adsorbed onto the liquid crystal–glycerol interface. It was shown that the photoisomerization processes of dendrimer molecules in a liquid crystal are accompanied by a spatial rearrangement of their azobenzene moieties, which is the key point in the explanation of the observed effects.
Keywords: dendrimer; droplets; nematic liquid crystal; orientational transition; photo-orientation

Smart Light-Responsive Materials: Azobenzene-Containing Polymers and Liquid Crystals - Zhao, Z.; Ikeda, T. (John Wiley & Sons, Inc., 2009)

(untitled) - Mahimwalla, Z.; Yager, K. G.; Mamiya, J.-i.; Shishido, A.; Priimagi, A.; Barrett, C. J. (Polym. Bull., 2012)

(untitled) - Bisoyi, H. K.; Li, Q. (Chem. Rev., 2016)

(untitled) - Seki, T. (J. Mater. Chem. C, 2016)

(untitled) - Cigl, M.; Bubnov, A.; Kašpar, M.; Hampl, F.; Hamplová, V.; Pacherová, O.; Svoboda, J. (J. Mater. Chem. C, 2016)

(untitled) - Bobrovsky, A.; Shibaev, V.; Piryazev, A.; Anokhin, D. V.; Ivanov, D. A.; Sinitsyna, O.; Hamplova, V.; Kaspar, M.; Bubnov, A. (Macromol. Chem. Phys., 2017)

(untitled) - Ikeda, T. (J. Mater. Chem., 2003)

(untitled) - Menzel, A. M. (Phys. Rep., 2015)

(untitled) - Ube, T.; Kawasaki, K.; Ikeda, T. (Adv. Mater., 2016)

(untitled) - Zakrevskyy, Y.; Richter, M.; Zakrevska, S.; Lomadze, N.; von Klitzing, R.; Santer, S. (Adv. Funct. Mater., 2012)

(untitled) - Schimka, S.; Lomadze, N.; Rabe, M.; Kopyshev, A.; Lehmann, M.; von Klitzing, R.; Rumyantsev, A. M.; Kramarenko, E. Yu.; Santer, S. (Phys. Chem. Chem. Phys., 2017)

(untitled) - Zhao, Y. (Macromolecules, 2012)

(untitled) - Lund, R.; Brun, G.; Chevallier, E.; Narayanan, T.; Tribet, C. (Langmuir, 2016)

(untitled) - Khoo, I. C. (Phys. Rep., 2009)

(untitled) - Shibaev, V.; Bobrovsky, A.; Boiko, N. (Prog. Polym. Sci., 2003)

(untitled) - Bubnov, A.; Iwan, A.; Cigl, M.; Boharewicz, B.; Tazbir, I.; Wójcik, K.; Sikora, A.; Hamplová, V. (RSC Adv., 2016)

(untitled) - Bobrovsky, A.; Shibaev, V.; Cigl, M.; Hamplová, V.; Pociecha, D.; Bubnov, A. (J. Polym. Sci., Part A: Polym. Chem., 2016)

(untitled) - Bobrovsky, A.; Shibaev, V.; Piryazev, A.; Anokhin, D. V.; Ivanov, D. A.; Sinitsyna, O.; Hamplova, V.; Kaspar, M.; Bubnov, A. (Macromol. Chem. Phys., 2017)

(untitled) - Palto, S. P.; Yudin, S. G.; Germain, C.; Durand, G. (J. Phys. II, 1995)

(untitled) - Palto, S. P.; Draginda, Y. A.; Artemov, V. V.; Gorkunov, M. V. J. (2017)

(untitled) - Budagovsky, I. A.; Ochkin, V. N.; Shvetsov, S. A.; Zolot’ko, A. S.; Bobrovsky, A. Y.; Boiko, N. I.; Shibaev, V. P. (Phys. Rev. E, 2017)

(untitled) - Momoi, Y.; Kwak, M.; Choi, D.; Choi, Y.; Jeong, K.; Koda, T.; Haba, O.; Yonetake, K. (J. Soc. Inf. Disp., 2012)

(untitled) - Nádasi, H.; Stannarius, R.; Eremin, A.; Ito, A.; Ishikawa, K.; Haba, O.; Yonetake, K.; Takezoe, H.; Araoka, F. (Phys. Chem. Chem. Phys., 2017)

(untitled) - Ouskova, E.; Vapaavuori, J.; Kaivola, M. (Opt. Mater. Express, 2011)

(untitled) - Ouskova, E.; Kaivola, M. (Opt. Mater. Express, 2012)

(untitled) - Komitov, L.; Ruslim, C.; Matsuzawa, Y.; Ichimura, K. (Liq. Cryst., 2000)

(untitled) - Yaroshchuk, O.; Reznikov, Y. (J. Mater. Chem., 2012)

(untitled) - Lee, G.; Araoka, F.; Ishikawa, K.; Momoi, Y.; Haba, O.; Yonetake, K.; Takezoe, H. (Part. Part. Syst. Charact., 2013)

(untitled) - Wang, X.; Bukusoglu, E.; Abbott, N. L. (Chem. Mater., 2017)

(untitled) - Shvetsov, S. A.; Emelyanenko, A. V.; Boiko, N. I.; Liu, J.-H.; Khokhlov, A. R. (J. Chem. Phys., 2017)

(untitled) - Hu, Q.-Z.; Jang, C.-H. (Soft Matter, 2013)

(untitled) - Han, G.-R.; Jang, C.-H. (Talanta, 2014)

(untitled) - Wang, Y.; Hu, Q.; Tian, T.; Yu, L. (Sens. Actuators, B, 2017)

(untitled) - Krakhalev, M. N.; Prishchepa, O. O.; Sutormin, V. S.; Zyryanov, V. Y. (Liq. Cryst., 2017)

(untitled) - Rudyak, V. Yu.; Krakhalev, M. N.; Prishchepa, O. O.; Sutormin, V. S.; Emelyanenko, A. V.; Zyryanov, V. Ya. (JETP Lett., 2017)

(untitled) - Lavrentovich, O. D. (Phys. Rev. A, 1992)

(untitled) - Kalugin, A. G. (Fluid Dyn., 2015)

Silicon-Containing Dendritic Polymers - Shibaev, V.; Boiko, N. (Liquid Crystalline Silicon-Containing Dendrimers with Terminal Mesogenic Groups, 2009)

(untitled) - Budagovsky, I. A.; Zolot’ko, A. S.; Smayev, M. P.; Shvetsov, S. A.; Boiko, N. I. (Bull. Lebedev Phys. Inst., 2016)

(untitled) - Statman, D.; Jánossy, I. (J. Chem. Phys., 2003)

(untitled) - Kalinin, N. V.; Emelyanenko, A. V.; Liu, J.-H. (Phase Transitions, 2017)

(untitled) - Dubtsov, A. V.; Pasechnik, S. V.; Shmeliova, D. V.; Kralj, S. (Appl. Phys. Lett., 2014)

(untitled) - Dubtsov, A. V.; Pasechnik, S. V.; Shmeliova, D. V.; Semerenko, D. A.; Iglič, A.; Kralj, S. (Liq. Cryst., 2017)

(untitled) - Lysachkov, A. I.; Boiko, N. I.; Rebrov, E. A.; Muzafarov, A. M.; Shibaev, V. P. (Russ. Chem. Bull., 2007)

(untitled) - Zolot’ko, A. S.; Budagovsky, I. A.; Ochkin, V. N.; Smayev, M. P.; Bobrovsky, A. Yu.; Shibaev, V. P.; Boiko, N. I.; Lysachkov, A. I.; Barnik, M. I. (Mol. Cryst. Liq. Cryst., 2008)

(untitled) - Jánossy, I.; Szabados, L. (J. Nonlinear Opt. Phys. Mater., 1998)

Physical Properties of Liquid Crystals - Demus, D.; Goodby, J.; Gray, G. W.; Spiess, H.-W.; Vill, V. (Wiley-VCH Verlag GmbH, 1999)

(untitled) - Fisher, E. (J. Phys. Chem., 1967)